To catch a raven - Jenkins, Beverly, 1951- (Jenkins, Beverly, 1951- Women who dare, 2022)
When the Declaration of Independence is stolen by a former Confederate official, fearless grifter Raven Moreaux, forced by the government to get it back, finds both her life and heart on the line when she falls for her partner who is posing as her husband.